Quantitative immunoelectrophoretic analysis in patients with tuberculosis and sarcoidosis. Issue 4 (July 1970) - Clarke, H. G. Minchin; Freeman, T.; Hickman, R.; Pryse-Phillips, W. E. M.
Abstract : A study of 12 immunologically distinct serum proteins has been made in two conditions, tuberculosis and sarcoidosis, which have in common the formation of giant-cell granulomata. Significantly (p <0·001) higher concentrations of five proteins [α2 group component (GC), caeruloplasmin (caer), haptoglobin (hpt), haemopexin (hpx), and α1 easily precipitable glycoprotein (α1 PGp)] were found in tuberculosis. No significant differences from normal were found in patients with sarcoidosis. The results obtained compared to the available figures for conventional electrophoresis and the so-called `acute phase reaction' are discussed.